2014
DOI: 10.1093/sysbio/syu054
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast Phylogenomic Analyses Resolve Deep-Level Relationships of an Intractable Bamboo Tribe Arundinarieae (Poaceae)

Abstract: The temperate woody bamboos constitute a distinct tribe Arundinarieae (Poaceae: Bambusoideae) with high species diversity. Estimating phylogenetic relationships among the 11 major lineages of Arundinarieae has been particularly difficult, owing to a possible rapid radiation and the extremely low rate of sequence divergence. Here, we explore the use of chloroplast genome sequencing for phylogenetic inference. We sampled 25 species (22 temperate bamboos and 3 outgroups) for the complete genome representing eight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

30
238
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(271 citation statements)
references
References 76 publications
30
238
3
Order By: Relevance
“…Ampelocalamus naibunensis is distantly related to A. calcareus, the earliest divergent lineage (XI) of Arundinarieae (Zhang et al 2016b). The phylogenetic relationships of the 11 major lineages (I to XI) of Arundinarieae recovered here is congruent with Ma et al (2014 The short internodes connected by long branches in the ML tree suggested a probable recent rapid radiation of Arundinarieae (Zhang et al 2016b). …”
supporting
confidence: 73%
“…Ampelocalamus naibunensis is distantly related to A. calcareus, the earliest divergent lineage (XI) of Arundinarieae (Zhang et al 2016b). The phylogenetic relationships of the 11 major lineages (I to XI) of Arundinarieae recovered here is congruent with Ma et al (2014 The short internodes connected by long branches in the ML tree suggested a probable recent rapid radiation of Arundinarieae (Zhang et al 2016b). …”
supporting
confidence: 73%
“…However, at the plant species-level plastome exons can be remarkably conserved (or even non-variant) causing sequence alignments to be non-informative. In addition, exon coding regions can be prone to selective and functional constraints that could cause a functional rather than historic signal to be tracked (Ma et al 2014;Rockenbach et al 2016), something to which non-coding regions will not be susceptible. Therefore, aiming for as complete as possible plastomes in genome-skimming phylogenetic projects will pay-off in the longer term.…”
Section: Iterative Organelle Genome Assemblymentioning
confidence: 99%
“…"A". calcareus is in a position unrelated to other species of Ampelocalamus in the phylogenies of Yang et al (2013) and Ma et al (2014), and is thus placed in Clade XI of the Arundinarieae; in the latter phylogeny it is sister to all other species of the tribe. The species is poorly known and is not given a full description here, nor is it placed in the key pending more comprehensive analysis.…”
Section: Shibataea Makino Ex Nakaimentioning
confidence: 97%
“…Culm internodes not alternating in length; bud prophylls triangular; culm leaf blades reflexed; spikelets not clustered 4 4 (3). Foliage leaves dimorphic, the blades of those on the main culm much larger than the ones on the lateral branches; leaf sheaths with fused fimbriae creating a This tribe includes all the temperate woody bamboos, and is monophyletic in all molecular phylogenies (Bamboo Phylogeny Group 2012; Burke et al 2012;Ma et al 2014;Zhang et al 2012. Leptomorph rhizomes may be a synapomorphy for this clade, but if so then the character has apparently reversed in some taxa.…”
mentioning
confidence: 99%
See 1 more Smart Citation